Smart recycle dustbin detector for cleaners in UiTM TapahCampus / Fatina Aisya Shuhaimi, Zalikha Zulkifli and Faridah Zulkipli - Shuhaimi, Fatina Aisya; Zulkifli, Zalikha; Zulkipli, Faridah (Universiti Teknologi MARA, Perak, 2018)
Commonly, when ask about cleaner's profession they always relate in maintaining quality environment. Overflowed of garbage in recycled bin always been an issue in the institution and the hazardous scenario in the institution leaving bad impression to the outsider such as parents and visitors. In order to overcome such overflowed of garbage in recycled bin issue and improving the cleaner efficiency in collecting the recycle materials from the recycle dustbin, Smart Recycle Dustbin Detector for cleaners is propose for this project. These smart recycle bin are in design phase and the bin are interfaced with "Exponent Client" application using react native on mobile application which the system working under the same Wi-Fi module. Hence, the status of full dustbins was sent to the cleaner's Apple iOS application using Wi-Fi module. The main objective of this project is to reduce human resources and efforts in collecting recycle materials along with the improvement of an institution's environment with technology applied in the institution vision.